2019
DOI: 10.3390/atmos11010049
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of PMV Model: Reliability, Implementation and Design of Software for Its Calculation

Abstract: In most countries, PMV is the reference index for the assessment of thermal comfort conditions in mechanically conditioned environments. It is also the basis to settle input values of the operative temperature for heating and cooling load calculations, sizing of equipment, and energy calculations according to EN 16798-1 and 16798-2 Standards. Over the years, great effort has been spent to study the reliability of PMV, whereas few investigations were addressed to its calculation. To study this issue, the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…PMV was used when ENVI-met as an assessment tool that models all outdoor environment element, didn't have the PET yet. In the previous versions of ENVI-met it used an improved PMV for outdoor conditions after the work of Jendritzky and Nübler to account for the outdoor wind speed and all net wave radiation [47], however, much discussion can be found in the work of d'Ambrosio et al, for the calculation issues of the original Fanger PMV [48]. Considering that the three design suggestions have 8 cm grass and 15 m height Ficus elastica trees, the results of this study showed that the first design suggestion reduced the external thermal comfort with range 0.1-0.7 than the base case.…”
Section: The Clustered Urban Form: From Cairo To Aswanmentioning
confidence: 99%
See 1 more Smart Citation
“…PMV was used when ENVI-met as an assessment tool that models all outdoor environment element, didn't have the PET yet. In the previous versions of ENVI-met it used an improved PMV for outdoor conditions after the work of Jendritzky and Nübler to account for the outdoor wind speed and all net wave radiation [47], however, much discussion can be found in the work of d'Ambrosio et al, for the calculation issues of the original Fanger PMV [48]. Considering that the three design suggestions have 8 cm grass and 15 m height Ficus elastica trees, the results of this study showed that the first design suggestion reduced the external thermal comfort with range 0.1-0.7 than the base case.…”
Section: The Clustered Urban Form: From Cairo To Aswanmentioning
confidence: 99%
“…2 (DS2) is a newly designed clustered housing with adjusted aspect ratios and green infra over a new vehicular network, whereas DS3 is the same as DS2 but with higher albedo for building surfaces and asphalt roads. It has to be noted that curves in Figure 2 report modified PMV values according to Jendritzki and Nubler [47].…”
Section: Connecting Outdoor-indoor Environmentsmentioning
confidence: 99%
“…The PMV value was calculated using the “calcPMV” function in R package “comf”, which applies the same calculations as Fanger [12] and ISO 7730 [20] . Alternative algorithms or softwares can be used to carry out the PMV calculation ( [9] and ASHRAE Standard-55 [3] , and a careful consideration of relative air velocity in the PMV calculation is required under high metabolic rates d’Ambrosio Alfano et al [8] , [9] ). We have assumed that the optimal air temperature T opt or PMV opt can be defined as the neutral condition at which a minimal percentage of people dissatisfied (PPD) can be achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, uncertainty in measurements must be also considered as well as in surveys of subjective occupant's evaluation [30]. On top of that, the recent advance in computational capacity has brought a catalogue of calculation tools for the PMV not only for personal computers, but also for smartphones, whose oversimplification in both the input data and the calculation procedure might lead to wrong results [31].…”
Section: Thermal Comfort Models: Adaptive and Staticmentioning
confidence: 99%
“…In contrast, adaptive comfort models have been developed in offices without HVAC systems (i.e., free-running offices), where occupants can freely interact with the building to achieve thermal comfort, either by opening or closing windows, changing their clothes or having cold drinks; in short, occupants are able to adapt, to a certain extent, to the internal ambient temperature [31,32].…”
Section: Thermal Comfort Models: Adaptive and Staticmentioning
confidence: 99%